2018
DOI: 10.33258/birle.v1i1.80
|View full text |Cite
|
Sign up to set email alerts
|

Culture Repertoire in Expressive Written Language : Study of Hypothesis of Edward Sapir and Benyamin Lee Whorf

Abstract: Language, culture, and mind are closely related, each of these extracts reflects one another. The relationship between language, culture and mind of speakers is a basic idea of Sapir and Whorf's theories and hypotheses. Language politeness that is rooted in the splash of the cultural values of the speaking community, including can be seen from the packaging of the information structure as outlined in the sentence of a language. The construction of different clauses grammatically packs different information str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…The content of the core material needed according to the perceptions of BIPA teachers and foreign speakers includes (1) dialogue and reading, (2) enrichment, and (3) grammar. Syahrin (2018) stated that the study of language and culture in general is focused on ideas, conceptions and beliefs that humans have, but not to cover everything that people do. Because not everything that people do can have an interesting relationship with language.…”
Section: A Materials or Content Rulesmentioning
confidence: 99%
“…The content of the core material needed according to the perceptions of BIPA teachers and foreign speakers includes (1) dialogue and reading, (2) enrichment, and (3) grammar. Syahrin (2018) stated that the study of language and culture in general is focused on ideas, conceptions and beliefs that humans have, but not to cover everything that people do. Because not everything that people do can have an interesting relationship with language.…”
Section: A Materials or Content Rulesmentioning
confidence: 99%
“…A change of behavior. Syahrin (2018) states that Language is a medium of communication between humans. Language is needed by humans because human language can find their needs by communicating.…”
Section: Learning Englishmentioning
confidence: 99%
“…Meanwhile (Barrie & Li, 2012) (Barrie & Li, 2012) tried to explore Noun Incorporation in non-canonical languages and found that Noun Incorporation in these languages is also a syntactic process and does not show a morphological process. Language is defined as a purely human and non-instinctive method of communicating ideas, emotions, and desires through a system of voluntarily produced symbols, according to (Syahrin, 2018) First and foremost, language is an auditory representational system of symbols. Language maintenance is cumpolsory responsibility of the users of the language .…”
Section: Introductionmentioning
confidence: 99%